Effects of probiotic supplementation on platelet morphology in overweight/obese woman - Veličković, Ksenija; Okuka, Nina; Polovina, Snežana; Sumarac-Dumanović, Mirjana; Ivanović, Nevena; Milinković, Neda; Djordjević, Brižita (Archives of Pharmacy, 2022)
Obesity could be associated with enhanced platelet (PL) function and thrombosis. Also, changes in gut microbiota composition were observed in obese patients, and probiotics supplementation has been shown to improve some of the obesity-associated metabolic parameters. This study aimed to determine the possible effects of probiotic supplementation on platelet morphology in overweight/obese premenopausal women.Twenty overweight (BMI = 25.0-29.9 kg/m2) and obese (BMI ≥ 30.0 kg/m2) women participated in double-blind, randomized, placebo-controlled study. They were randomly assigned to receive one capsule daily of probiotics (7x1010 CFU Lactobacillus plantarum 299v (DSM9843), 5x109 CFU Saccharomyces cerevisiae var. boulardii and 40mg octacosanol; N=10) or placebo (N=10) for 3 months. To determine changes in the parameters of platelet activation - the platelet count (PC), platelet distribution width (PDW), Feret diameter, and hypogranular appearance, blood samples were obtained for an automated hematology analyser and peripheral smears staining. Although difference in PC was not found between groups, supplementation with probiotics decreased PDW compared to the placebo group (p